Kemampuan Pemecahan Masalah Pembuktian Siswa SMP Berbantuan Geogebra - Hikmah, Fita Amidanal; Rosyidi, Abdul Haris (MATHEdunesa, 2025)
Proof problem solving ability is an important part of the independent curriculum. However in reality, this ability is difficult for students to master because students are still unable to connect known facts with the elements to be proven so the need for the use of tools to improve students' problem solving skills. Geogebra can also facilitate students in every stage of solving proof problems. This research is a qualitative descriptive research that aims to describe the problem solving ability of Geogebra-assisted junior high school students. The subjects of this study were 4 students including 2 students with high ability and 2 students with moderate ability. The results showed that at the stage of understanding the problem, students with high and medium mathematical abilities could identify the information given. Although at first students with moderate ability experienced misunderstandings, these students could realize the misunderstanding with the help of Geogebra. Geogebra is very useful in helping students to understand the meaning of the problem and makes it easy to make visualizations quickly and accurately. At the stage of developing a solution plan, students can make several plans. With the help of Geogebra, students with moderate ability can determine the solution steps that are more precise and easy to understand. In addition, with Geogebra students can help to bring up concept ideas in problem solving. At the stage of implementing the plan, students with moderate ability have difficulty in implementing the plan, but with the help of Geogebra, students with moderate ability can re-examine the visualization results to get a new plan. Students use Geogebra to explore the plans that have been made to find the solution steps. At the stage of re-examining the solution, only students with high ability see the correctness of the results for all situations.